Seed morphological traits and germination of Peltogyne mexicana (Fabaceae), unique Peltogyne species in Mexico - Basave-Villalobos, Erickson; Antúnez, Pablo; Sigala Rodríguez, José Ángel; Fierros-Mateo, Reynol; Navarro-Martínez, José; Calixto Valencia, Celi Gloria (Instituto de Ecología, A.C., 2024)
Background and Aims: Peltogyne mexicana is the only species of the genus Peltogyne in Mexico, but its natural populations are subject to fragmentation processes and conservation strategies are needed. Nursery propagation can contribute to the conservation of the species, but appropriate germplasm management strategies must be developed. It is important to know the morphological characteristics of the seeds and their germination. The objectives of this work were: (1) to characterize the intrapopulation variation of some morphological traits (qualitative and morphometric) of P. mexicana seeds, and (2) to analyze the influence of size on germination.Methods: Traits such as color, shape, length, width, thickness, and weight of seeds of individuals of P. mexicana were described and characterized. The relationship between traits was examined with a Pearson correlation analysis and intrapopulation variation was tested with an analysis of variance. The influence of size on germination was also analyzed using logistic regression and the Weibull function, in all cases at a significance level of 5%.Key results: The seeds of P. mexicana are dark red with an ovoid shape. There is a high intrapopulation variation in traits. Width is the trait with the least variation, weight varies the most. All traits are significantly correlated with each other, but length and weight have the highest degree of association. Germination is significantly related to seed weight. The probability of germination increases as weight also increases. High germination rates occur for seeds weighing 0.65 g and germination occurs most frequently at 11.20 days.Conclusions: Seed morphological traits of P. mexicana vary intrapopulationally. Seed weight influences germination.